Incidental findings on brain MRI in patients with first-episode and chronic psychosis. (October 2022) - Bellani, Marcella; Perlini, Cinzia; Zovetti, Niccolò; Rossetti, Maria Gloria; Alessandrini, Franco; Barillari, Marco; Ricciardi, Giuseppe Kenneth; Konze, Angela; Sberna, Maurizio; Zoccatelli, Giada; Lasalvia, Antonio; Miceli, Maurizio; et al.
Highlights: Brain incidental findings are more frequent in psychotic patients. Periventricular white matter hyperintensities are characteristic of chronic patients. Hyperintensities and ventricular asymmetries are found in first-episode patients. We indicate possible vulnerability factors preceeding the onset of psychosis. Abstract: Brain incidental findings (IFs) are unexpected brain abnormalities detected by a structural magnetic resonance (MRI) examination. We conducted a study to assess whether brain IFs are associated with first-episode psychosis (FEP) and chronic psychosis (affective vs. non-affective) compared to healthy controls (HC). Chi-squared analyses were run to compare the frequency of several IFs across groups. Logistic regression analyses were run to explore the association between group and IFs, accounting for sex, age, MRI field strength. We observed a higher frequency of most IFs in both FEP and chronic psychosis groups compared to HC, however most of the chi-squared tests did not reach significance. Patients with FEP and chronic psychosis were 3–4 times more likely to show deep white matter hyperintensities (WMH) than HC. Patients with FEP and affective chronic psychosis were 3–4 times more likely to show ventricular asymmetries than HC. All chronic patients were more likely to show periventricular WMH, liquoral spaces enlargements and ventricular system enlargements respectively. Our results suggest that deep WMH and ventricular asymmetries are associated with both the early and the chronic stages of psychosis, thus representing potential vulnerability factors already present before the onset of the symptoms, possibly due to neurodevelopmental insults.